Analysis of the level of gender inequality in the labor market in kazakhstan (Journal of Economic Research & Business Administration, 2023)
The purpose of this study is to assess the level of gender differences in the labour market of Kazakhstan before and after the COVID-19 pandemic. The relevance of the study is provided by the need to investigate the causes of gender differences and gender discrimination in the labour market and the importance of developing measures to improve gender policy. The paper raises the issue of women's opportunities and rights in the labour market to effectively use women's potential for the country's benefit. A literary review has shown that a special place among various works is occupied by an approach that focuses on the influence of the social structure of society on the relationship between the sexes, the empirical basis of which is the results of specific sociological studies. This study is based on complex approaches, such as systematisation and grouping of statistical data. Statistical data were taken for 2018-2021 from the Bureau of National Statistics by gender. The developed methodological tools will allow for a reliable and formalised analysis of the gender pay gap and identify the main determinants of gender pay differences. The proposed indicators differ in the regional level's availability and the possibility of analyzing indicators. The results of the study showed the current state of the labour market in the gender context, and it was revealed that women's labour is less in demand and valuable than men's labour. The study results can serve as a scientific justification for implementing an effective policy in the field of women's empowerment in the labour market.